Implementasi Sistem Informasi Pemerintah Daerah Republik Indonesia (SIPD RI) (Studi Kasus Pada Kantor Kecamatan Sumbersari Di Kabupaten Jember) - Oryza Ardhiarisca; Dafillah Vike Eryana; Berlina Yudha Pratiwi; Siska Aprilia Oktaviani (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2026)
This study aims to analyse the implementation of the Local Government Information System of the Republic ofIndonesia (SIPD RI) at the Sumbersari Sub-district Office in Jember Regency. The method used in this studyis qualitative descriptive, with data collected through interviews. The results of the study indicate that theimplementation of SIPD RI at the Sumbersari Sub-district Office in Jember Regency has not yet been fullyoptimised. This is due to several obstacles in its implementation. In terms of communication, theimplementation of SIPD RI has been running smoothly, as evidenced by effective communication between theHead of the Planning and Finance Sub-Division, staff, and relevant parties, thereby supporting the smoothrunning of policies and minimising obstacles in the implementation process. However, in terms of resources,the implementation of SIPD RI has not been optimal due to ongoing issues with equipment, such as technicalsystem faults and inadequate internet connectivity. In terms of disposition, the implementation of SIPD RI hasalso not been maximised as there are still challenges regarding user understanding, such as a lack ofattention to detail during the data entry process. Furthermore, in terms of bureaucratic structure, theimplementation of SIPD RI has not been optimal due to the absence of specific written Standard OperatingProcedures (SOPs) regarding the use of SIPD RI.